Origins, Worlds, and Life: Planetary Science and Astrobiology in the Next Decade - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The next decade of planetary science and astrobiology holds tremendous promise. This booklet highlights key science questions, identifies priority missions, and presents a research strategy that includes both planetary defense and human exploration.
Keywords: Space and Aeronautics

Plasma Science: Enabling Technology, Sustainability, Security, and Exploration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Plasma Science and Engineering transforms fundamental scientific research into powerful societal applications, from materials processing and healthcare to forecasting space weather. Plasma Science: Enabling Technology, Sustainability, Security and Exploration discusses the importance of plasma research, identifies important grand challenges for the next decade, and makes recommendations on funding and workforce. This publication will help federal agencies, policymakers, and academic leadership understand the importance of plasma research and make informed decisions about plasma science funding, workforce, and research directions.
Keywords: Math, Chemistry, and Physics; Space and Aeronautics

Assessment of Commercial Space Platforms for Earth Science Instruments: Report Series—Committee on Earth Science and Applications from Space - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Space-based Earth observations enable global observations of the land surface, biosphere, solid Earth, atmosphere, cryosphere, and oceans. Earth observations from space, combined with data acquired from in situ and ground-based instruments, help scientists understand the components of the Earth system and their interactions and enable wide-ranging applications, including forecasts of weather and air quality, projections of future climate, management of natural resources, ecological forecasting, disaster management, drought and wildfire prediction, and the mapping and prediction of vector borne/animal diseases. At the request of NASA Earth Science Division, this report assesses the potential use of a proposed multi-user, robot-tended, uncrewed commercial space platform as a potential host for a large number of Earth remote sensing instruments. Assessment of Commercial Space Platforms for Earth Science Instruments evaluates the utility and practicality of a platform in a Sun-synchronous orbit, capable of hosting 20 or more instruments.
Keywords: Space and Aeronautics

Foundations of a Healthy and Vital Research Community for NASA Science - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The U.S. space science community includes thousands of scientists across multiple disciplines that influence and are influenced by the many engineers, technicians, and support personnel that are part of the space research enterprise. Over one-third of NASA's budget is devoted to space science, and the agency currently operates over 50 space missions in the fields of astrophysics, Earth science, solar and space physics, planetary science, and the biological and physical sciences. The strength of NASA science lies with its people, both those who work directly for the agency and the thousands of researchers and professionals who are funded by NASA grants and contracts. At the request of NASA, this report examines the foundation for healthy and vital research communities. Foundations of a Healthy and Vital Research Community for NASA Science identifies the characteristics of a healthy and vital research community, defines implementable measures for assessing the health and vitality of a research community, describes the types of data that NASA should be collecting to enable future assessments of the health and vitality of the scientific work force, and recommends best practices to improve the health and vitality of NASA’s research communities.
Keywords: Space and Aeronautics

Flying in the COVID-19 Era: Science-based Risk Assessments and Mitigation Strategies on the Ground and in the Air: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The National Academies of Sciences, Engineering, and Medicine convened a workshop on February 4th and 5th, 2021 to review the issues related to safety of passengers and employees in commercial air transportation, for domestic and international travel, during the COVID-19 pandemic. The workshop explored best practices to assess and mitigate COVID-19 transmission risks experienced during the travel chain, from the departure airport entrance to the destination airport exit. The workshop also identified areas where more research is needed to address gaps in understanding. This publication documents the presentations and discussions held during the workshop, and is presented as a synthesis of the workshop.
Keywords: Space and Aeronautics

Airborne Platforms to Advance NASA Earth System Science Priorities: Assessing the Future Need for a Large Aircraft - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The National Aeronautics and Space Administration (NASA) and other U.S. science research agencies operate a fleet of research aircraft and other airborne platforms that offer diverse capabilities. To inform NASA's future investments in airborne platforms, this study examines whether a large aircraft that would replace the current NASA DC-8 is needed to address Earth system science questions, and the role of other airborne platforms for achieving future Earth system science research goals.
Keywords: Space and Aeronautics; Earth Sciences

Review of the Space Communications Program of NASA's Space Operations Mission Directorate - National Research Council (The National Academies Press, 2007)
The Space Communications Office (SCO) at NASA has two primary roles. The first is to manage two of the communications networks that enable spaceflight operations and research, and the second is to integrate agency-wide telecommunications issues. In 2005, NASA asked the NRC to review the effectiveness of the SCO in carrying out its responsibilities by assessing the overall quality of the space communications program. This report presents a review of each of the program elements within the SCO—the space network, NASA’s integrated space network (NISN), spectrum management, standards management, search and rescue, communications and navigation architecture, technology, and operations integration. The review focuses on formulation of plans for each element, plan development methodology, connections with the broader community, and overall capabilities. Recommendations for improving SCO operations and organization are provided.
Keywords: Space and Aeronautics

Report Series: Committee on Biological and Physical Sciences in Space: Using Commercial Lunar Payload Services (CLPS) to Achieve Lunar Biological and Physical Science Objectives: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
After several decades since the last human visit, NASA is planning to return to the Moon, this time not only to visit but also to carry out extensive scientific experiments, establish a habitat occupied by astronauts, and learn lessons that will help in preparations for the eventual establishment of a human presence on Mars. The Commercial Lunar Payload Services (CLPS) program, overseen by NASA, will provide transport to the Moon for scientists who want to carry out research on the lunar surface or in orbit around the Moon. Recognizing the need to introduce and explain the CLPS program to researchers, the Committee on Biological and Physical Sciences in Space of the National Academies of Sciences, Engineering, and Medicine held a workshop on March 24-25, 2021 entitled "Using Commercial Lunar Payload Services (CLPS) to Achieve Lunar Biological and Physical Science Objectives". The organization of the workshop was guided by the following question: Looking at the period of time prior to the release of the next decadal survey, how can this community support and utilize CLPS to address areas of research? This workshop proceedings summarizes the presentations and discussions from the workshop sessions.
Keywords: Space and Aeronautics

Origins, Worlds, and Life: A Decadal Strategy for Planetary Science and Astrobiology 2023-2032 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The next decade of planetary science and astrobiology holds tremendous promise. New research will expand our understanding of our solar system's origins, how planets form and evolve, under what conditions life can survive, and where to find potentially habitable environments in our solar system and beyond. Origins, Worlds, and Life: A Decadal Strategy for Planetary Science and Astrobiology 2023-2032 highlights key science questions, identifies priority missions, and presents a comprehensive research strategy that includes both planetary defense and human exploration. This report also recommends ways to support the profession as well as the technologies and infrastructure needed to carry out the science.
Keywords: Space and Aeronautics

Exoplanet Science Strategy - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The past decade has delivered remarkable discoveries in the study of exoplanets. Hand-in-hand with these advances, a theoretical understanding of the myriad of processes that dictate the formation and evolution of planets has matured, spurred on by the avalanche of unexpected discoveries. Appreciation of the factors that make a planet hospitable to life has grown in sophistication, as has understanding of the context for biosignatures, the remotely detectable aspects of a planet's atmosphere or surface that reveal the presence of life. Exoplanet Science Strategy highlights strategic priorities for large, coordinated efforts that will support the scientific goals of the broad exoplanet science community. This report outlines a strategic plan that will answer lingering questions through a combination of large, ambitious community-supported efforts and support for diverse, creative, community-driven investigator research.
Keywords: Space and Aeronautics

Powering Science: NASA's Large Strategic Science Missions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
NASA's Science Mission Directorate (SMD) currently operates over five dozen missions, with approximately two dozen additional missions in development. These missions span the scientific fields associated with SMD's four divisions—Astrophysics, Earth Science, Heliophysics, and Planetary Sciences. Because a single mission can consist of multiple spacecraft, NASA-SMD is responsible for nearly 100 operational spacecraft. The most high profile of these are the large strategic missions, often referred to as "flagships." Large strategic missions are essential to maintaining the global leadership of the United States in space exploration and in science because only the United States has the budget, technology, and trained personnel in multiple scientific fields to conduct missions that attract a range of international partners. This report examines the role of large, strategic missions within a balanced program across NASA-SMD space and Earth sciences programs. It considers the role and scientific productivity of such missions in advancing science, technology and the long-term health of the field, and provides guidance that NASA can use to help set the priority of larger missions within a properly balanced program containing a range of mission classes.
Keywords: Space and Aeronautics

Review of the Draft 2014 Science Mission Directorate Science Plan - National Research Council (The National Academies Press, 2013)
NASA's Science Mission Directorate (SMD) is engaged in the final stages of a comprehensive, agency-wide effort to develop a new strategic plan at a time when its budget is under considerable stress. SMD's Science Plan serves to provide more detail on its four traditional science disciplines - astronomy and astrophysics, solar and space physics (also called heliophysics), planetary science, and Earth remote sensing and related activities - than is possible in the agency-wide Strategic Plan. Review of the Draft 2014 Science Mission Directorate Science Plan comments on the responsiveness of SMD's Science Plan to the National Research Council's guidance on key science issues and opportunities in recent NRC decadal reports. This study focuses on attention to interdisciplinary aspects and overall scientific balance; identification and exposition of important opportunities for partnerships as well as education and public outreach; and integration of technology development with the science program. The report provides detailed findings and recommendations relating to the draft Science Plan.
Keywords: Space and Aeronautics

Review of the Draft 2019 Science Mission Directorate Science Plan - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
NASA’s Science Mission Directorate (SMD) ties together diverse researchers, sponsors, and resources to develop the science community’s understanding of the universe. Within scientific organizations like NASA, it is important to establish clear strategies and goals to guide research and foster new discoveries across varying missions. SMD created a draft for their 2019 Science Plan, and a review of this draft is necessary to ensure that the plan establishes clear, attainable, relevant, and ambitious goals. Review of the Draft 2019 Science Mission Directorate Science Plan provides comments on and recommendations for SMD’s draft. Comments in this report focus on the level of ambition of the specified strategies in light of current and emerging opportunities to advance Earth and space science over the next 5 years, the ability of SMD to meet the science objectives in the most recent decadal surveys through implementation of specified strategies, additional strategies for SMD’s considerations, and the general readability and clarity of the draft. Recommendations in this report identify important improvements for the 2019 Science Plan.
Keywords: Space and Aeronautics

Report Series: Committee on Astrobiology and Planetary Science: Review of the Planetary Science Aspects of NASA SMD's Lunar Science and Exploration Initiative - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On December 11, 2017, President Donald Trump signed Space Policy Directive-1 (SPD-1). The new directive replaced original text in the National Space Policy of the United States of America and instructed the Administrator of the National Aeronautics and Space Administration (NASA) to “lead the return of humans to the Moon for long-term exploration and utilization, followed by human missions to Mars and other destinations”. In response to and in support of the vision expressed in SPD-1, this report reviews decadal and other community-guided lunar science priorities as context for NASA’s current lunar plans and then presents and evaluates the actions being taken by NASA’s Planetary Science Division to support lunar science.
Keywords: Space and Aeronautics

Report Series: Committee on Astrobiology and Planetary Science: Getting Ready for the Next Planetary Science Decadal Survey - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
This study discusses the publicly available studies of future flagship- and New Frontiers-class missions NASA initiated since the completion of Vision and Voyages. The report considers the priority areas as defined in Vision and Voyages where publicly available mission studies have not been undertaken; appropriate mechanisms by which mission-study gaps might be filled in the near- to mid-term future; and other activities that might be undertaken in the near- to mid-term future to optimize and/or expedite the work of the next planetary science decadal survey committee.
Keywords: Space and Aeronautics

Extending Science: NASA's Space Science Mission Extensions and the Senior Review Process - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
NASA operates a large number of space science missions, approximately three-quarters of which are currently in their extended operations phase. They represent not only a majority of operational space science missions, but a substantial national investment and vital national assets. They are tremendously scientifically productive, making many of the major discoveries that are reported in the media and that rewrite textbooks. Extending Science – NASA's Space Science Mission Extensions and the Senior Review Process evaluates the scientific benefits of missions extensions, the current process for extending missions, the current biennial requirement for senior reviews of mission extensions, the balance between starting new missions and extending operating missions, and potential innovative cost-reduction proposals for extended missions, and makes recommendations based on this review.
Keywords: Space and Aeronautics

An Assessment of the Science Proposed for the Deep Underground Science and Engineering Laboratory (DUSEL) - National Research Council (The National Academies Press, 2012)
According to the big bang theory, our Universe began in a state of unimaginably high energy and density, contained in a space of subatomic dimensions. At that time, unlike today, the fundamental forces of nature were presumably unified and the particles present were interacting at energies not attainable by present-day accelerators. Underground laboratories provide the conditions to investigate processes involving rare phenomena in matter and to detect the weak effects of highly elusive particles by replicating similar environments to those once harnessed during the earliest states of the Earth. These laboratories now appear to be the gateway to understanding the physics of the grand unification of the forces of nature. Built to shield extremely sensitive detectors from the noise of their surroundings and the signals associated with cosmic rays, underground facilities have been established during the last 30 years at a number of sites worldwide. To date, the United States' efforts to develop such facilities have been modest and consist primarily of small underground laboratories. However, the U.S. underground community has pushed for larger underground facilities on the scale of major laboratories in other countries. An Assessment of the Deep Underground Science and Engineering Laboratory (DUSEL) addresses this matter by evaluating the major physics questions and experiments that could be explored with the proposed DUSEL. Measuring the potential impact, this assessment also examines the broader effects of the DUSEL in regards to education and public outreach, and evaluates the need associated with developing U.S. programs similar to science programs in other regions of the world.
Keywords: Math, Chemistry, and Physics; Engineering and Technology; Space and Aeronautics

Report Series: Committee on Astrobiology and Planetary Science: Review of the Commercial Aspects of NASA SMD's Lunar Science and Exploration Initiative - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On December 11, 2017, President Donald Trump signed Space Policy Directive-1 (SPD-1). The new directive replaced original text in the National Space Policy of the United States of America and instructed the Administrator of the National Aeronautics and Space Administration (NASA) to "lead the return of humans to the Moon for long-term exploration and utilization, followed by human missions to Mars and other destinations". In response to and in support of the vision expressed in SPD-1, the first report reviewed decadal and other community-guided lunar science priorities as context for NASA’s current lunar plans and then presented and evaluated the actions being taken by NASA’s Planetary Science Division (PSD) to support lunar science. At the request of NASA PSD, this second report explores plans for commercial partnerships, lunar infrastructure development, and related aspects of NASA’s lunar science and exploration initiative.
Keywords: Space and Aeronautics

Achieving Science with CubeSats: Thinking Inside the Box - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Space-based observations have transformed our understanding of Earth, its environment, the solar system and the universe at large. During past decades, driven by increasingly advanced science questions, space observatories have become more sophisticated and more complex, with costs often growing to billions of dollars. Although these kinds of ever-more-sophisticated missions will continue into the future, small satellites, ranging in mass between 500 kg to 0.1 kg, are gaining momentum as an additional means to address targeted science questions in a rapid, and possibly more affordable, manner. Within the category of small satellites, CubeSats have emerged as a space-platform defined in terms of (10 cm x 10 cm x 10 cm)- sized cubic units of approximately 1.3 kg each called "U's." Historically, CubeSats were developed as training projects to expose students to the challenges of real-world engineering practices and system design. Yet, their use has rapidly spread within academia, industry, and government agencies both nationally and internationally. In particular, CubeSats have caught the attention of parts of the U.S. space science community, which sees this platform, despite its inherent constraints, as a way to affordably access space and perform unique measurements of scientific value. The first science results from such CubeSats have only recently become available; however, questions remain regarding the scientific potential and technological promise of CubeSats in the future. Achieving Science with CubeSats reviews the current state of the scientific potential and technological promise of CubeSats. This report focuses on the platform's promise to obtain high- priority science data, as defined in recent decadal surveys in astronomy and astrophysics, Earth science and applications from space, planetary science, and solar and space physics (heliophysics); the science priorities identified in the 2014 NASA Science Plan; and the potential for CubeSats to advance biology and microgravity research. It provides a list of sample science goals for CubeSats, many of which address targeted science, often in coordination with other spacecraft, or use "sacrificial," or high-risk, orbits that lead to the demise of the satellite after critical data have been collected. Other goals relate to the use of CubeSats as constellations or swarms deploying tens to hundreds of CubeSats that function as one distributed array of measurements.
Keywords: Space and Aeronautics

Review of the Restructured Research and Analysis Programs of NASA's Planetary Science Division - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The Research and Analysis (R&A) program managed by NASA's Planetary Science Division (PSD), supports a broad range of planetary science activities, including the analysis of data from past and current spacecraft; laboratory research; theoretical, modeling, and computational studies; geological and astrobiological fieldwork in planetary analog environments on Earth; geological mapping of planetary bodies; analysis of data from Earth- and space-based telescopes; and development of flight instruments and technology needed for future planetary science missions. The primary role of the PSD R&A program is to address NASA's strategic objective for planetary science and PSD's science goals. Recently, PSD reorganized the R&A program to provide better alignment with the strategic goals for planetary sciences. The major changes in the R&A program involved consolidating a number of prior program elements, many of which were organized by subdiscipline, into a smaller number of thematic core research program elements. Despite numerous efforts by PSD to communicate the rationale for the reorganization and articulate clearly the new processes, there has been significant resistance from the planetary science community and concerns in some sectors regarding the major realignment of funding priorities. Review of NASA's Planetary Science Division's Restructured Research and Analysis Programs examines the new R&A program and determines if it appropriately aligns with the agency's strategic goals, supports existing flight programs, and enables future missions. This report explores whether any specific research areas or subdisciplinary groups that are critical to NASA's strategic objectives for planetary science and PSD's science goals are not supported appropriately in the current program or have been inadvertently disenfranchised through the reorganization.
Keywords: Space and Aeronautics